Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Solve boolean algebra rule: A+ĀB=A+B.I want its explaination how it can be derived... I mean L.H.S=R.H.S

Solve boolean algebra rule: A+ĀB=A+B.I want its explaination how it can be derived... I mean L.H.S=R.H.S

Grade:12th pass

1 Answers

Vaidehi
45 Points
3 years ago
by distributive law A+(B.C)=(A+B).(B+C) 
apply the same here Ā).(A+B)=1.(A+B)=(A+B) ;(Since A+Ā=1)A+ĀB=(A+
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free